Implementasi Pembelajaran Tahfidz Al-Qur’an dengan Menggunakan Metode Tasmi’ di SMP Islam Al-Ishlah Bukittinggi - Aulia Rizki Fadhila; Amar Husni; Wedra Aprison; Iswantir M (Departement of Mathematics Education, 2023)
The purpose of this study was to identify (1) Implementation of learning tahfidz Al-Qur'an using the tasmi' method (2) Supporting and inhibiting factors for learning tahfidz Al-Qur'an using the tasmi' method. This study uses a qualitative approach using descriptive methods. Researchers collect data through observation, interviews, and documentation. Data were analyzed in three stages, namely data reduction, data presentation, and data verification. The technique of guaranteeing the validity of the data is by using source triangulation. Based on the results of the research that the researchers conducted, it can be interpreted that: 1) Implementation consists of planning, implementation, and evaluation, namely (a) Planning for learning Alqur'an tahfidz using the tasmi' method consists of 4 steps, namely planning objectives, materials, methods used will be carried out and assessed. (b) The implementation of learning Al-Qur'an tahfidz using the tasmi' method is that students do tasmi' when they have memorized 5 corners/pages. For tasmi' 1 juz, there are 4 meetings. Learning activities are carried out 2 times a week. (c) Evaluation of Al-Qur'an tahfidz learning using the tasmi' method is carried out by evaluating the objectives, materials, methods, and assessment of its implementation. 2) The supporting factors and inhibiting factors in learning tahfidz Al-Qur'an using the tasmi' method come from students, namely intelligence, intention, and willingness to memorize the Al-Qur'an.